Graphene film lithography equipment

By introducing an intermediate layer, such as zirconium dioxide or molybdenum silicide in the catalyst, the problems of uneven surface and uneven thickness of graphene in the prior art are solved, and more uniform and stable graphene is produced, suitable for EUV surface films. Improves the operating stability of the equipment and the service life of the diaphragm.

CN111836681BActive Publication Date: 2025-02-18ASML NETHERLANDS BV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN201980018223.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-14
Filing Date
2019-02-07
Publication Date
2025-02-18
Estimated Expiration
2039-02-07

AI Technical Summary

Technical Problem

The prior art is difficult to produce graphene with high surface uniformity and high thickness uniformity, resulting in graphene separators that are prone to breaking in EUV lithography equipment and need to be replaced frequently.

Method used

Using a catalyst including an intermediate layer, which may be a metal oxide, such as zirconium dioxide, or a metal silicide, such as molybdenum silicide, or carbon, for the production of graphene. The intermediate layer provides a smoother surface by affecting the growth of molybdenum and the formation of molybdenum carbide, improving the quality of graphene.

Benefits of technology

By using a catalyst including an intermediate layer, the produced graphene layer is more uniform and has a more consistent thickness. It is suitable for use in EUV surface films, improving the thermal stability and strength of graphene and extending the service life of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111836681B_ABST
    Figure CN111836681B_ABST
Patent Text Reader

Abstract

A catalyst is disclosed, comprising: a first layer, the first layer comprising molybdenum; a base layer; and an intermediate layer, wherein the intermediate layer is disposed between the base layer and the first layer. Also disclosed are methods for preparing the catalyst and methods for synthesizing graphene, surface films produced using the catalyst or the method disclosed herein, and lithographic equipment comprising such films.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to European application No. 18160866.2 filed on March 9, 2018 and European application No. 18212646.6 filed on December 14, 2018, the entire contents of which are incorporated herein by reference. Technical Field

[0003] The present invention relates to a catalyst. In particular, the present invention relates to a catalyst for producing graphene, wherein the produced graphene is suitable for EUV mask. The present invention also relates to using boron nitride to cover the surface film. Background Art

[0004] A lithographic apparatus is a machine configured to apply a desired pattern to a substrate. A lithographic apparatus may be used, for example, in the manufacture of integrated circuits (ICs). A lithographic apparatus may, for example, project a pattern at a patterning device (e.g., a mask) onto a layer of radiation-sensitive material (resist) disposed on a substrate.

[0005] To project a pattern onto a substrate, a lithographic apparatus may use electromagnetic radiation. The wavelength of this radiation determines the minimum size of a feature that can be formed on a substrate. A lithographic apparatus using extreme ultraviolet (EUV) radiation with a wavelength in the range of 4 nm to 20 nm (e.g., 6.7 nm or 13.5 nm) may be used to form smaller features on a substrate compared to a lithographic apparatus using, for example, radiation with a wavelength of 193 nm.

[0006] In a lithographic apparatus, EUV radiation is generated by ionizing droplets of liquid tin by a radiation source such as a laser. The liquid tin droplets pass in front of the radiation source, and when the radiation hits the tin droplets, the tin droplets are ionized and release EUV radiation. One problem associated with generating EUV radiation in this way is that the tin may contaminate various components of the lithographic apparatus, such as the patterning device.

[0007] The pattern forming device suitable for use in the lithographic apparatus may be a mask. The mask may become contaminated by particles or contaminants from inside the lithographic apparatus. Particles may contaminate one or more of the front side of the mask, the back side of the mask, and the side and / or edge of the mask. The particles may be generated by the interaction of the fixture on the side of the mask, or may come from any other source, such as inorganic contaminants derived from the gas used in the lithographic apparatus, resist debris sputtered from the substrate during exposure, or mechanical contact between parts of the equipment. Contaminants may include metal or metal oxide particles.

[0008] The problem of reticle contamination is particularly relevant to extreme ultraviolet (EUV) lithography. Protective elements can usually be used to protect the reticle from contamination within the lithographic apparatus. However, in EUV lithography, certain protective elements cannot be used due to the wavelength of the EUV radiation used.

[0009] The protective element may include a pellicle. A pellicle is a thin, substantially transparent (at least to EUV radiation) membrane that prevents contamination of the EUV reticle. A pellicle suitable for use with EUV radiation needs to have high EUV transparency so that the EUV radiation is not absorbed by the EUV pellicle. The EUV pellicle also needs to have high thermal resistance. The EUV pellicle also needs to have high strength. The EUV pellicle may break during use due to the high temperatures experienced by the EUV pellicle.

[0010] Due to the low absorption rate of graphene to EUV radiation and the strength properties of graphene, graphene has been found to be a useful material for incorporation into EUV pellicles. In addition, graphene EUV pellicles can be produced as very thin membranes. However, the strength of thin graphene diaphragms depends on the uniformity of the graphene surface and the uniformity of the thickness of the thin graphene diaphragm. Rough graphene surface layers and thickness variations may introduce weaknesses into the graphene diaphragm structure. Weak points in the graphene diaphragm may cause the thin graphene diaphragm to break, and therefore require more frequent replacement.

[0011] Since the discovery of graphene, several methods have been explored to produce high-quality materials. Existing methods for synthesizing single-layer graphene and few-layer graphene membranes include carbon vapor deposition (CVD), in which a carbon source is deposited onto a surface. However, the challenge has been to provide a surface on which thin-layer graphene membranes, including multiple layers, can be grown quickly and reliably.

[0012] Molybdenum catalysts supported on silicon wafers have been used for the synthesis of graphene layers. Compared to other transition metals, molybdenum provides a thermal expansion coefficient comparable to silicon, thereby causing less thermal stress. Silicon wafers have also been thermally oxidized so that molybdenum is supported on a thin silicon dioxide surface layer (also known as a thermal oxide layer) of the silicon wafer. Although the exact catalytic mechanism is not yet clear, when the catalyst is used, the molybdenum is converted into molybdenum carbide, which is believed to then act as a catalyst.

[0013] However, current methods for producing graphene layers for use in EUV pellicles typically result in non-smooth graphene surfaces, membranes of variable thickness, and irregular, heterogeneous morphologies. This makes graphene produced using known catalysts and known methods less suitable for use as EUV pellicles.

[0014] Therefore, there is a need to produce graphene with high surface uniformity and high thickness uniformity. In addition, there is a need to provide wafer-level graphene without defects throughout the entire graphene layer. Graphene membranes with such properties have suitably high thermal stability, are suitably EUV transparent, and have high strength to be used in EUV pellicles.

[0015] It would therefore be desirable to provide improved methods for producing graphene suitable for use as pellicles.

[0016] The pellicle may be etched in an atmosphere containing free radical species such as H* and HO*, and thus the pellicle may degrade over time in use. Since the pellicle is very thin, the reaction with the free radical species may weaken the pellicle and eventually render it ineffective.

[0017] It would therefore be desirable to provide skin films having improved chemical and thermal stability compared to known films.

[0018] Although the present application generally relates to pellicles in the context of lithographic apparatus, and in particular EUV lithographic apparatus, the present invention is not limited to pellicles and lithographic apparatus, and it will be appreciated that the subject matter of the present invention may be used in any other suitable apparatus or situation.

[0019] For example, the method of the invention may be equally applied to spectral purity filters. Practical EUV sources, such as those using plasma to generate EUV radiation, emit not only desired "in-band" EUV radiation, but also undesired (out-of-band) radiation. This out-of-band radiation is most notably in the deep UV (DUV) radiation range (100 nm to 400 nm). Furthermore, in the case of some EUV sources, such as laser-produced plasma EUV sources, the radiation from the laser, typically at 10.6 microns, exhibits significant out-of-band radiation.

[0020] In lithographic equipment, spectral purity is desired for several reasons. One reason is that the resist is sensitive to out-of-band wavelengths of radiation, and thus the image quality of the pattern applied to the resist may degrade if the resist is exposed to such out-of-band radiation. In addition, out-of-band radiation infrared radiation, such as the 10.6 micron radiation in some laser-generated plasma sources, causes unwanted and unnecessary heating of the pattern forming device, substrate and optical devices within the lithographic equipment. Such heating may cause damage to these components, degradation of their lifetime, and / or defects or deformations in the pattern projected onto and applied to the substrate coated with the resist.

[0021] A typical spectral purity filter may, for example, be formed from a silicon infrastructure (e.g. a silicon grid, or other component provided with holes) coated with a reflective metal such as molybdenum. In use, a typical spectral purity filter may be subjected to high heat loads from, for example, incident infrared and EUV radiation. The heat load may cause the temperature of the spectral purity filter to be above 800°C. Delamination / demixing and degradation of the silicon infrastructure is accelerated by the presence of hydrogen, which is often used as a gas in the environment in which the spectral purity filter is used in order to inhibit debris (e.g. debris such as particles etc.) from entering or leaving certain parts of the lithographic apparatus. Thus, a spectral purity filter may be used as a pellicle, and vice versa. Therefore, references to a "pellicle" in this application are also references to a "spectral purity filter". Although reference is primarily made to a pellicle in this application, all features may equally apply to a spectral purity filter.

[0022] In a lithographic apparatus (and / or method), it is desirable to minimize the loss of intensity of radiation being used to apply a pattern to a resist-coated substrate. One reason for this is that ideally, as much radiation as possible should be available to apply the pattern to the substrate, for example to reduce exposure time and increase throughput. At the same time, it is desirable to minimize the amount of undesired radiation (e.g. out-of-band radiation) that passes through the lithographic apparatus and impinges on the substrate. Furthermore, it is desirable to ensure that a spectral purity filter used in a lithographic method or apparatus has an appropriate lifetime and does not degrade rapidly over time due to high heat loads to which the spectral purity filter may be exposed and / or hydrogen (etc., such as free radical active species including H* and HO*) to which the spectral purity filter may be exposed. It is therefore desirable to provide an improved (or alternative) spectral purity filter, and for example to provide a spectral purity filter suitable for use in a lithographic apparatus and / or method. Summary of the invention

[0023] The present invention has been made in view of the aforementioned problems using known catalysts and methods for producing graphene films.

[0024] According to a first aspect of the present invention, there is provided a catalyst comprising: (i) a first layer comprising a transition metal; (ii) a base layer; and (iii) an intermediate layer, wherein the intermediate layer is disposed between the base layer and the first layer. The transition metal may be, for example, selected from the group consisting of molybdenum, tungsten, platinum, copper and nickel.

[0025] Without wishing to be bound by theory, it is believed that irregularities in graphene, such as surface defects and variable thickness, are caused by poor surface uniformity of the catalyst used during synthesis. The first layer of catalyst comprises an active catalyst or a catalyst precursor. The present invention provides an intermediate layer disposed between the base layer and the first layer, which results in a smoother surface of the catalytic second layer, and thus higher quality graphene.

[0026] In some embodiments, the intermediate layer may include a metal oxide. Preferably, the intermediate layer includes zirconium dioxide.

[0027] Zirconium dioxide has been found to exhibit the greatest benefit, while oxides of other metals such as titanium, hafnium, copper, aluminum, manganese and silver exhibit slightly lesser benefits.

[0028] Without wishing to be bound by theory, it is believed that the crystal structure of the intermediate layer provides a favorable lattice surface with which the crystal structure of molybdenum can interact. Specifically, it is believed that the presence of an intermediate layer between the substrate and the molybdenum provides a surface with a reduced number of defects. In addition, without wishing to be bound by theory, it is believed that zirconium dioxide can interact with molybdenum and act as a co-catalyst or promoter. The intermediate layer affects the growth of molybdenum during the deposition of molybdenum when the catalyst is being produced. The intermediate layer also affects the formation of molybdenum carbide. The intermediate layer also affects the growth of graphene on the catalyst. It has been found that multilayer graphene grows more rapidly on a catalyst comprising an intermediate layer compared to a known catalyst comprising a molybdenum layer on a silicon substrate which itself may include a silicon dioxide layer.

[0029] Alternatively or additionally, the intermediate layer may include a metal silicide. The metal silicide may be a silicide of any suitable metal, but is preferably molybdenum silicide. It has been found that the presence of a metal silicide (particularly molybdenum silicide) intermediate layer accelerates the growth of graphene multilayers on the catalyst.

[0030] Additionally or alternatively, the intermediate layer may also include carbon. The carbon may be amorphous carbon (aC). It has been unexpectedly discovered that amorphous carbon, when deposited on a molybdenum catalyst, will be converted into graphene when heated to from about 800°C to about 1000°C, preferably about 900°C.

[0031] In some embodiments, the base layer includes silicon. The silicon may also include silicon dioxide. The silicon dioxide may be in a layer. The intermediate layer is preferably disposed on the silicon or silicon dioxide layer.

[0032] The first layer may include a transition metal, for example selected from the group consisting of molybdenum, tungsten, platinum, copper and nickel.

[0033] In an embodiment, the first layer may include metallic or elemental molybdenum. The first layer may include molybdenum carbide. In the case where the first layer includes metallic or elemental molybdenum, when the catalyst is used to produce graphene, the molybdenum will form molybdenum carbide. Thus, reference to a first layer including molybdenum encompasses both the case where the molybdenum is in its metallic or elemental form, and the case where the molybdenum is in its molybdenum carbide form, or any intermediate position.

[0034] In a second aspect of the present invention, there is provided a method for preparing a catalyst, comprising the following steps:

[0035] (i) providing an intermediate layer comprising metal oxide, metal silicide and / or carbon on a base layer; and (ii) providing a first layer comprising a transition metal, for example selected from the group consisting of molybdenum, tungsten, platinum, copper and nickel.

[0036] Preferably, the intermediate layer comprises zirconium. Preferably, the intermediate layer comprises zirconium dioxide.

[0037] In an embodiment, the intermediate layer includes molybdenum silicide.

[0038] In an embodiment, the intermediate layer comprises carbon, preferably amorphous carbon (aC).

[0039] The intermediate layer may be formed by sputtering, chemical vapor deposition or any other suitable method. The intermediate layer may be provided by sputtering from a zirconium target, a zirconium oxide target or by cross sputtering. In the presence of oxygen, the intermediate layer may be provided by sputtering zirconium. The oxygen may be in any suitable form, such as a neutral or ionized gas or plasma.

[0040] The first layer may be formed by sputtering, chemical vapor deposition or any other suitable method.

[0041] The substrate may be any substrate disclosed herein. The substrate preferably comprises silicon, but any other suitable substrate may be used.

[0042] According to a third aspect of the present invention, a method for synthesizing graphene is provided, comprising the following steps: depositing carbon onto the surface of a catalyst according to the first aspect of the present invention or prepared by the method according to the second aspect of the present invention; and forming a graphene layer on the catalyst.

[0043] Although the catalyst for producing graphene is known, it has been unexpectedly found that the catalyst including the intermediate layer of metal oxide or silicide provides improved performance. In an experiment using the same conditions (such as temperature, pressure and carbon source), it was found that when using the catalyst of the prior art, the thickness of the multilayer graphene layer was about 6.5nm after 90 minutes. In contrast, the catalyst according to the present invention forms a multilayer graphene layer with a thickness between about 17nm and about 18.5nm after 90 minutes under the same conditions. In addition, compared with the graphene grown on the catalyst of the prior art, the graphene is significantly more uniform when grown on the catalyst according to the present invention. In addition, XRD studies have determined that when compared with growing the molybdenum layer without the intermediate layer, the zirconium dioxide layer affects the growth of the molybdenum layer, thereby resulting in a higher crystal orientation. It is believed that this at least partially provides the improved performance exhibited by the catalyst according to the present invention.

[0044] In some embodiments of the method according to the third aspect of the present invention, the base layer comprises silicon. In some embodiments, the base layer further comprises silicon dioxide. In some embodiments, one or more of the first layer and the intermediate layer is formed by sputtering.

[0045] The method may also include removing graphene from the surface of the catalyst. Compared to multilayer graphene produced using catalysts of the prior art, the multilayer graphene produced is more uniform in thickness. This makes the multilayer graphene produced using the catalyst or method of the present invention particularly suitable for use in pellicles, such as EUV pellicles.

[0046] In certain embodiments, the carbon source is provided as a carbon-containing gas or as a carbon stream. Any suitable carbon-containing gas can be used, such as (for example) hydrocarbon gas, such as methane or ethane. The carbon-containing gas can be saturated or unsaturated. Unsaturated gases include ethylene and acetylene, which can be particularly desired due to their increased reactivity and lower hydrogen content. The temperature and pressure used can be selected from any suitable parameters, which will be known to those skilled in the art.

[0047] The carbon may be deposited by means of carbon vapor deposition. The carbon may be deposited at any suitable temperature. Suitable temperatures may range from about 700°C to about 100°C.

[0048] It has been unexpectedly recognized that it is possible to grow graphene layers on a catalyst without using chemical vapor deposition. In conventional methods, graphite multilayers are grown on a catalyst at a temperature in the range of about 800°C to about 1000°C. Carbon is provided via a carbon-containing gas such as methane in the presence of hydrogen and argon (but any rare gas, such as helium, or other inert gas may be used). It has been unexpectedly recognized that it is possible to grow graphene without using chemical vapor deposition. It has been recognized that it is possible to convert an amorphous carbon layer into a graphene layer by depositing an amorphous carbon layer on a catalyst and then heating the amorphous carbon and catalyst to a temperature from about 800°C to about 1000°C, preferably about 900°C, so as to convert the amorphous carbon into graphene.

[0049] In one method, an amorphous carbon layer with a layer thickness ranging from 1nm to 1000nm, preferably ranging from 10nm to 600nm, is deposited on a molybdenum layer and subsequently annealed. The annealing may occur at a temperature of from about 800°C to about 1000°C, preferably about 900°C, so as to convert amorphous carbon into graphene. The annealing time may be in the range of 1 minute to 180 minutes, preferably 5 minutes to 60 minutes. Annealing may occur in a hydrogen / argon atmosphere. Molybdenum may be supported on a silicon-based layer that may include silicon dioxide. The catalyst on which amorphous carbon is deposited may be a catalyst according to any aspect of the present invention. In this embodiment, the thickness of the catalyst or catalyst layer may be in the range of from 5nm to 1000nm, preferably from 20nm to 800nm. For example, when copper is used as a catalyst, the thickness of the catalyst layer is preferably in the range of from 100nm to 1000nm, more preferably in the range of from 400nm to 900nm, to provide a thicker catalyst layer. Such a catalyst layer may be applied on top of, below or even on both sides of the amorphous carbon layer.It should be noted that within the meaning of the present invention, the catalyst according to the present invention may also be referred to as a catalyst layer.

[0050] In another aspect, the amorphous carbon layer is deposited between the base layer and the molybdenum layer. The base layer may include silicon, which may include silicon dioxide. The catalyst having the amorphous carbon deposited thereon may be a catalyst according to any aspect of the present invention.

[0051] The amorphous carbon may be deposited by any suitable method such as, for example, sputtering. This method allows the production of multilayer graphene without the need for CVD equipment. This method allows the use of an annealing oven to produce graphene.

[0052] According to a fourth aspect of the present invention, there is provided a method for using the catalyst or method according to the first, second or third aspect of the present invention in synthesizing graphene. Preferably, the graphene is multilayer graphene.

[0053] According to a fifth aspect of the present invention, there is provided a surface film comprising graphene produced according to any aspect of the present invention.

[0054] Compared to graphene produced using known catalysts, the graphene produced using the catalyst of the present invention is more uniform in thickness, which makes the graphene extremely suitable for use in pellicles, especially EUV pellicles.

[0055] The surface film may include a cover layer and a surface film core. Preferably, the cover layer substantially covers the surface film core.

[0056] The cap layer can be any suitable material. The cap material can include molybdenum, aluminum, ruthenium and molybdenum, molybdenum and boron, zirconium and boron, yttrium and boron, or lanthanum and boron. The cap layer can include any of the aforementioned metals with boron carbide or boron nitride. The cap layer can include zirconium boride, molybdenum boride, yttrium boride, molybdenum silicide, yttrium silicide, zirconium dioxide, molybdenum oxide, yttrium oxide, diamond-like carbon, niobium oxide, carbon nitride, silicon nitride, molybdenum carbide, zirconium carbide, yttrium carbide, silicon carbide, zirconium nitride or aluminum oxide.

[0057] In some embodiments, the cap layer comprises boron nitride, preferably boron nitride with a hexagonal crystal structure. In other embodiments, the boron nitride is amorphous or cubic boron nitride. The choice of which crystal structure of boron nitride (i.e., cubic, hexagonal or amorphous) is used depends on the crystal structure of the core material to provide the best match. The crystal structure can be adjusted by adjusting the deposition method and any post-deposition treatment. For example, hexagonal boron nitride may be preferred to grow on graphene by means of chemical vapor deposition. Cubic boron nitride can be grown by plasma assisted vapor deposition or physical vapor deposition with subsequent plasma treatment. Cubic boron nitride will mechanically best match cubic crystals such as molybdenum silicide.

[0058] Boron nitride can be used to cover the surface film core materials including graphene, molybdenum silicide, molybdenum silicide nitride, zirconium silicide, zirconium silicide nitride, boron and silicon nitride. These surface film cores can also be covered by any of the aforementioned cover layer materials.

[0059] In some embodiments, the EUV pellicle core comprises graphene produced according to the method according to any aspect of the present invention.

[0060] According to a sixth aspect of the present invention, there is provided an EUV lithography apparatus comprising the EUV pellicle according to the fifth aspect of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Embodiments of the invention will now be described, by way of example only, with reference to the accompanying schematic drawings, in which:

[0062] Figure 1 Describing a lithographic system including a lithographic apparatus and a radiation source;

[0063] Figure 2 depicts a schematic cross section through a catalyst according to the invention showing an intermediate layer;

[0064] Figure 3a and Figure 3b shows a comparison of the surface of a multi-layer graphene layer produced using a catalyst of the prior art and a catalyst according to the present invention; and

[0065] Figure 4a and Figure 4b Depicted is a schematic cross section through a catalyst comprising an amorphous carbon layer according to the present invention. DETAILED DESCRIPTION

[0066] Figure 1 A lithographic system is shown comprising a radiation source SO and a lithographic apparatus LA. The radiation source SO is configured to generate an EUV radiation beam B and to supply the EUV radiation beam B to the lithographic apparatus LA. The lithographic apparatus LA comprises an illumination system IL, a support structure MT configured to support a patterning device MA (e.g. a mask), a projection system PS, and a substrate table WT configured to support a substrate W.

[0067] The illumination system IL is configured to condition the EUV radiation beam B before it is incident on the patterning device MA. In addition, the illumination system IL may include a faceted field mirror arrangement 10 and a faceted pupil mirror arrangement 11. The faceted field mirror arrangement 10 and the faceted pupil mirror arrangement 11 together provide a desired cross-sectional shape and a desired intensity distribution to the EUV radiation beam B. In addition to the faceted field mirror arrangement 10 and the faceted pupil mirror arrangement 11, or instead of the faceted field mirror arrangement 10 and the faceted pupil mirror arrangement 11, the illumination system IL may also include other mirrors or arrangements.

[0068] After being so conditioned, the EUV radiation beam B interacts with the patterning device MA. As a result of this interaction, a patterned EUV radiation beam B' is produced. The projection system PS is configured to project the patterned EUV radiation beam B' onto a substrate W. For this purpose, the projection system PS may include a plurality of mirrors 13, 14 configured to project the patterned EUV radiation beam B' onto a substrate W held by a substrate table WT. The projection system PS may apply a reduction factor to the patterned EUV radiation beam B', thereby forming an image having features that are smaller than corresponding features on the patterning device MA. For example, a reduction factor of 4 or 8 may be applied. Although the projection system PS is illustrated as having only Figure 1 1 , but the projection system PS may comprise a different number of mirrors (eg six or eight mirrors).

[0069] The substrate W may include a previously formed pattern. In this case, the lithographic apparatus LA aligns an image formed by the patterned EUV radiation beam B′ with a pattern previously formed on the substrate W.

[0070] A relative vacuum, ie a small amount of gas (eg hydrogen) at a pressure well below atmospheric pressure, may be provided in the radiation source SO, in the illumination system IL, and / or in the projection system PS.

[0071] The radiation source SO may be a laser produced plasma (LPP) source, a discharge produced plasma (DPP) source, a free electron laser (FEL), or any other radiation source capable of producing EUV radiation.

[0072] Although EUV reticles are mentioned in the following description, any suitable patterning device MA may be used.

[0073] Example of laminate preparation according to the invention:

[0074] A p-type silicon (100) wafer with a resistivity between 20Ωcm and 30Ωcm covered with a thermally grown SiO2 film with a thickness of 500nm was used as a substrate substrate. On top of the silicon wafer, a double layer was deposited, either molybdenum on top of amorphous carbon or amorphous carbon on molybdenum, resulting in 4 samples. Sample 1 and sample 2 have molybdenum on top of the amorphous carbon layer. Sample 1 has a 500nm carbon layer and a 20nm molybdenum layer. Sample 2 has a 40nm carbon layer and a 20nm molybdenum layer. The order of layers in the stack of sample 1 and sample 2 is: molybdenum, amorphous carbon, SiO2, c-Si. Sample 3 and sample 4 have amorphous carbon on top of molybdenum. Sample 3 has a 500nm carbon layer and a 50nm molybdenum layer. Sample 4 has a 40nm carbon layer and a 50nm molybdenum layer. The order of layers in the stack of sample 3 and sample 4 is: amorphous carbon, molybdenum, SiO2, c-Si. The molybdenum layer and the amorphous carbon layer are sputtered at room temperature from a target having a purity equal to 6N5 and 4N for Mo and C, respectively. For the growth of graphene, a thermal annealing up to 915° C. is performed. The annealing gas consists of a mixture of argon and hydrogen at a pressure of 25 mbar.

[0075] The temperature curve has a ramp curve in three stages and starts with a slow heating to 915°C in the first stage to reduce thermal stress in the silicon and molybdenum layers. The first stage is the fastest stage, with a rate of 200°C / min, rising from room temperature to 525°C. This is followed by the second stage, with a slower slope (50°C / min) until 725°C. The third heating rate is 30°C / min and continues until the final temperature (915°C) is reached. A 1-minute time interval is included between each heating stage to achieve temperature stability. Growth is performed at 915°C for different time windows. Cooling consists of a controlled cooling rate of 25°C / min until 525°C before the heater is completely turned off. Due to thermal inertia, cooling has an exponential curve. Annealing is performed in a mixture of argon and hydrogen. By changing the ratio and / or growth time of the two gases, the influence of the gas atmosphere on the growth process is studied. Table 1 shows the corresponding matching scheme.

[0076] It has been observed that for all four samples, graphene growth occurs when the catalyst layer is sputtered above or below the amorphous carbon layer. The growth mechanism involves diffusion of amorphous carbon within the catalyst layer, followed by carbon segregation and formation of graphene on top of the molybdenum layer. For samples 1 and 2, which start with a molybdenum layer on top of the amorphous carbon layer, after annealing, the order of layers in the stack becomes: graphene, Mo2C, amorphous carbon, SiO2, c-Si. For samples 3 and 4, which start with a molybdenum layer below the amorphous carbon layer, after annealing, the order of layers in the stack becomes: amorphous carbon, graphene, Mo2C, SiO2, c-Si.

[0077] Table 1. Options for graphene growth

[0078]

[0079] The highest quality of graphene confirmed by Raman spectroscopy and cross-sectional transmission electron microscopy TEM was obtained for sample 1, where a 20 nm thick molybdenum layer was deposited on a 500 nm thick amorphous carbon film. Based on the Raman spectroscopy results, the quality of the graphene layer was found to be at least as good as that obtained in conventional CVD deposition using a gaseous hydrocarbon source. The lowest temperature used to grow graphene was about 900°C.

[0080] In another embodiment of the invention, it was found to be advantageous to grow graphene using an intermediate annealing step, whereby the annealing process is divided into two stages: 1) a first annealing step of the stack of layers at a temperature of about 700° C., in order to produce carbides of the transition metal catalyst; and thereafter 2) a second annealing step for growing a graphene layer by annealing the stack of layers at about 900° C. It is presumed that this intermediate annealing step (first annealing step) allows a better redistribution of stresses in the stacked layers.

[0081] Figure 2 A schematic representation of a catalyst according to the present invention is depicted. The catalyst comprises a base layer 15, an intermediate layer 16 and a first layer 17. The intermediate layer 16 is deposited between the base layer 15 and the first layer 17 such that the intermediate layer 16 is arranged between the base layer 15 and the first layer 17.

[0082] The base layer 15 may be any suitable material, but preferably comprises silicon and more preferably is a silicon wafer. The base layer 15 may comprise a silicon dioxide layer (not shown), which may be referred to as a thermal oxide layer. The intermediate layer 16 and the thermal layer are preferably different.

[0083] In use, a carbon source is provided and the catalyst is heated to a temperature required for carbonizing or graphitizing the carbon source. When the carbon is deposited on the surface of the catalyst, the carbon forms a graphene layer. The length of time can be adjusted to produce a thicker or thinner graphite layer.

[0084] Figure 3a shows an optical microscope image at 100 times magnification of a graphene layer produced using a known catalyst without an intermediate layer, and Figure 3b An optical microscope image of a graphene layer produced using a catalyst according to the invention including an intermediate layer at 100 times magnification is shown. The graphene produced according to the invention clearly shows a much greater uniformity. In addition, the graphene layer is produced much more quickly than using catalysts according to the prior art, which leads to a shortened production time and a reduced thermal energy requirement.

[0085] Figure 4a and Figure 4b Two options for depositing amorphous carbon on the catalyst are shown. Specifically, Figure 4a An embodiment is shown where amorphous carbon 18 is deposited on top of a molybdenum layer 19. The molybdenum may be supported on a base layer 20, and there may be an intermediate layer (not shown) between the base layer 20 and the molybdenum layer 19. There may also be a thermal oxide (silicon dioxide layer) (not shown) on the surface of the base layer 20. Figure 4b An embodiment is shown in which amorphous carbon 18 is provided between a molybdenum layer 19 and a base layer 20 which may include silicon. The catalyst may be a catalyst according to any aspect of the present invention.

[0086] In use, the amorphous carbon is deposited by any suitable means, such as sputtering.The catalyst comprising the amorphous carbon is heated for a period of time sufficient to cause at least a portion of the amorphous carbon to be converted into graphene.

[0087] It was further found that for the graphene growth method according to the invention, other transition metals such as tungsten, platinum, copper and nickel are also suitable for use as catalyst layers. From the perspective of graphene quality and for the film manufacturing process flow, it was found that molybdenum catalysts provide particularly good results.

[0088] Even more surprisingly, in the method according to the invention, it was also found possible to first deposit a cap layer (e.g. silicon carbide) on top of the stack of layers comprising amorphous carbon / molybdenum and then grow graphene without CVD below the cap layer. This method allows eliminating the influence of the atmosphere in the deposition chamber on the graphene growth. This allows avoiding damage to the graphene layer that might occur by depositing the cap layer (i.e. when the cap layer would be deposited after the graphene growth). Although not yet fully understood in terms of the reaction mechanism, it was found that the graphene grown below the cap layer using the method of the invention showed a higher quality, which was detected by lower defect spikes in the Raman spectrum. Examples of cap layers that may be used in accordance with the present invention include, but are not limited to, cap layers comprising zirconium boride, molybdenum boride, yttrium boride, molybdenum silicide, yttrium silicide, zirconium dioxide, molybdenum oxide, yttrium oxide, diamond-like carbon, niobium oxide, carbon nitride, silicon nitride, molybdenum carbide, zirconium carbide, yttrium carbide, silicon carbide, zirconium nitride, or aluminum oxide.

[0089] Although specific embodiments of the present invention have been described above, it will be appreciated that the present invention may be practiced in other ways different from those described. The above description is intended to be illustrative, not restrictive. Thus, it will be appreciated by those skilled in the art that modifications may be made to the described invention without departing from the scope of the claims set forth below. Specifically, the features disclosed with respect to one aspect of the present invention may be combined with any other aspect of the present invention.

[0090] Although embodiments of the present invention may be specifically mentioned herein in the context of lithographic equipment, embodiments of the present invention may be used in other equipment. Embodiments of the present invention may form a component of a mask inspection device, a metrology device, or any device that measures or processes an object such as a wafer (or other substrate) or a mask (or other pattern forming device). These devices may be generally referred to as lithographic tools. Such lithographic tools may use vacuum conditions or ambient (non-vacuum) conditions.

[0091] Although specific reference may be made above to the use of embodiments of the invention in the context of optical lithography, it will be appreciated that the invention is not limited to optical lithography and may be used in other applications such as imprint lithography where the context permits.

Claims

1. A catalyst for producing graphene, the catalyst comprising: (i) a first layer comprising a transition metal; (ii) grass-roots level; and (iii) middle layer, wherein the intermediate layer is disposed between the base layer and the first layer, and the intermediate layer comprises a metal oxide and a metal silicide, the metal oxide comprises zirconium dioxide, the metal silicide comprises molybdenum silicide, The catalyst further comprises: (iv) an amorphous carbon layer deposited on the first layer. 2 . The catalyst according to claim 1 , wherein the transition metal in the first layer is selected from at least one of molybdenum, tungsten, platinum, copper and nickel. The catalyst according to claim 1 , wherein the substrate comprises silicon. The catalyst of claim 3 , wherein the substrate comprises silicon dioxide.

5. The catalyst of claim 1, wherein the first layer comprises elemental molybdenum and / or molybdenum carbide.

6. A method for preparing a catalyst for producing graphene, the method comprising the following steps: (i) providing an intermediate layer including a metal oxide and a metal silicide on the base layer, wherein the metal oxide includes zirconium dioxide and the metal silicide includes molybdenum silicide; (ii) providing a first layer including a transition metal; and (iii) depositing an amorphous carbon layer on the first layer. 7 . The method according to claim 6 , wherein at least one of the first layer and the intermediate layer is formed by sputtering or chemical vapor deposition.

8. A method for synthesizing graphene, comprising the following steps: (i) depositing carbon onto the surface of the catalyst according to any one of claims 1 to 5; and (ii) forming a graphene layer on the catalyst.

9. The method according to claim 8, wherein the carbon source is provided as a carbon-containing gas or as a carbon stream.

10. The method according to any one of claims 8 or 9, wherein the carbon layer is an amorphous carbon layer.

11. The method of claim 8, wherein the catalyst layer is disposed above and / or below the carbon layer.

12. The method of claim 8, wherein the carbon is deposited by a process other than chemical vapor deposition.

13. The method of claim 8, wherein the carbon layer deposited onto the surface of the catalyst is heated to form graphene.

14. The method according to claim 13, wherein the heating is performed at an annealing temperature in the range from 600°C to 1200°C.

15. The method of claim 13, wherein the heating comprises a first annealing step at a temperature in the range of 600°C to 800°C to produce a carbide of the transition metal catalyst.

16. The method of claim 13, wherein the heating comprises a second annealing step at a temperature in the range of 800°C to 1200°C to convert the carbon into graphene.

17. The method of claim 16, wherein the heating comprises a second annealing step at a temperature in the range from 900°C to 1100°C to convert the carbon into graphene.

18. The method of claim 8, comprising the intermediate step of providing a capping layer onto the carbon layer and the catalyst layer and then forming the graphene layer below the capping layer.

19. The method of claim 18, wherein the cap layer comprises at least one of: molybdenum, aluminum, a combination of ruthenium and molybdenum, a combination of molybdenum and boron, a combination of zirconium and boron, a combination of yttrium and boron, or a combination of lanthanum and boron.

20. The method of claim 18 or 19, wherein the cap layer comprises zirconium boride, molybdenum boride, yttrium boride, molybdenum silicide, yttrium silicide, zirconium dioxide, molybdenum oxide, yttrium oxide, diamond-like carbon, niobium oxide, carbon nitride, silicon nitride, molybdenum carbide, zirconium carbide, yttrium carbide, silicon carbide, zirconium nitride or aluminum oxide.

21. The method of claim 8, wherein the carbon layer has a thickness ranging from 1 nm to 1000 nm.

22. The method of claim 21, wherein the carbon layer has a thickness in the range from 10 nm to 600 nm.

23. The method of claim 8, wherein the catalyst layer has a thickness in a range from 5 nm to 1000 nm.

24. The method of claim 23, wherein the catalyst layer has a thickness in the range from 20 nm to 800 nm.

25. The method of claim 23, wherein when the catalyst comprises copper, the thickness of the catalyst layer ranges from 100 nm to 1000 nm.

26. The method of claim 23, wherein the thickness of the catalyst layer is in a range from 400 nm to 900 nm.

27. The method of claim 8, wherein the stack of all layers comprises: Amorphous carbon, graphene, Mo2C, SiO2 and c-Si.

28. The method of claim 8, further comprising removing the graphene layer from the catalyst surface.

29. A method for using the catalyst according to any one of claims 1 to 5 in the synthesis of graphene.

30. The use of the catalyst according to claim 29, wherein the graphene is multilayer graphene.

31. A surface film comprising graphene produced according to the method according to any one of claims 8 to 28.

32. The skin film according to claim 31, comprising a cover layer and a skin film core.

33. The skin film of claim 32, wherein the cover layer covers the skin film core.

34. The pellicle of claim 32, wherein the cover layer comprises at least one of: molybdenum, aluminum, a combination of ruthenium and molybdenum, a combination of molybdenum and boron, a combination of zirconium and boron, a combination of yttrium and boron, or a combination of lanthanum and boron.

35. The pellicle of claim 34, wherein the cover layer comprises at least one of zirconium boride, molybdenum boride, yttrium boride, molybdenum silicide, yttrium silicide, zirconium dioxide, molybdenum oxide, yttrium oxide, diamond-like carbon, niobium oxide, carbon nitride, silicon nitride, molybdenum carbide, zirconium carbide, yttrium carbide, silicon carbide, zirconium nitride or aluminum oxide.

36. The pellicle of claim 32, wherein the cap layer comprises one or more of the following: ruthenium, molybdenum, boron, yttrium, lanthanum, boron, zirconium, carbon, niobium, silicon, aluminum, nitrogen, or oxygen.

37. The pellicle of claim 36, wherein the cover layer is selected from one or more of the following: ruthenium, aluminum, a combination of ruthenium and molybdenum, a combination of molybdenum and boron, a combination of zirconium and boron, a combination of yttrium and boron, and a combination of lanthanum and boron.

38. The pellicle according to any one of claims 32 to 37, wherein the cover layer comprises boron carbide, silicon carbide and / or boron nitride.

39. The pellicle of claim 38, wherein the cover layer comprises boron nitride.

40. The pellicle of claim 39, wherein the boron nitride comprises a hexagonal crystal structure, a cubic crystal structure, or is amorphous.

41. The pellicle of claim 32, wherein the pellicle core comprises graphene produced according to the method of claim 8.

42. A lithographic apparatus comprising a pellicle according to any one of claims 31 to 41.

Citation Information

Patent Citations

  • Pellicle and method for manufacturing the same

    CN106997847A

  • Pellicle and method for manufacturing the same

    US20170205705A1